All‐in‐One Structured Lithium‐Metal Battery - Lei Dong; Chang Zhang; Wei Liu (Advanced Science, 2022)
Abstract 3D batteries possess apparent advantage in electrochemical ion‐transport kinetics than the conventional‐structured batteries. However, due to the special electrode configuration and fabrication complexity, 3D battery design has inherent issue of mechanical stability and only succeeds in microsystems, far from ideal. Herein, a high‐stable, all‐in‐one structured 3D lithium‐metal battery is designed which consists of paralleled microcell arrays. Fast ion‐transport kinetics in full cell level can not only address the key issue of lithium dendrites in anode but also improve electrochemical performance of cathode. As a result, the resultant lithium metal anode acquires long‐term stability of 1000‐cycle life at a high current density of 10 mA cm−2. Also the all‐in‐one structured lithium metal battery has general applicability for various cathodic materials and delivers significantly improved rate and cycling performance, as well as high areal capacity up to 10.4 mAh cm−2.